An Analysis of the Role of Youth in Shaping Political Dynamics in West Africa: Perspectives on Political Patronage and Youth Engagement in Guinea-Bissau - Seidi, Dembael; Paskarina, Caroline; Djuyandi, Yusa (GoAcademica Research & Publishing, 2025)
This research investigates the role of youth in shaping political dynamics in Guinea-Bissau, focusing on political patronage and youth engagement. Despite facing significant socio-economic challenges, such as high unemployment and limited access to quality education, young people in Guinea-Bissau actively engage in non-violent activities like sporting events, cultural days in schools, and community clean-ups, often supported by political parties. These activities reflect a shift towards constructive political participation, contrasting with the more violent demonstrations seen in neighboring countries. The study employs qualitative methods, including semi-structured interviews and content analysis, to gather and analyze data from Bissau-Guinean youth engaged in politics. The theoretical framework combines political patronage theory, youth political involvement, and democratic engagement to analyze how youth influence political dynamics. Findings reveal that patronage systems play a significant role in mediating youth political involvement, often reinforcing existing power structures and limiting genuine political participation. To enhance youth political involvement, the research underscores the need for investment in education, raising political awareness, and ensuring transparency to reduce corruption and promote informed debates. Drawing on qualitative data from interviews and thematic analysis, the study provides a nuanced understanding of the unique historical, socio-economic, and cultural contexts influencing youth political engagement in Guinea-Bissau. The findings offer valuable insights for policymakers, practitioners, and scholars, emphasizing the importance of inclusive and effective political processes to foster democratic governance and political stability in the region. This research aims to fill the gap in existing literature by providing a focused analysis of youth political engagement in Guinea-Bissau, contributing to the broader discourse on youth political participation in West Africa.